Serum Bisphenol A Level in Boys with Cryptorchidism: A Step to Male Infertility? - Marta Diana Komarowska; Adam Hermanowicz; Urszula Czyzewska; Robert Milewski; Ewa Matuszczak; Wojciech Miltyk; Wojciech Debek (International Journal of Endocrinology)
Cryptorchidism is the most common congenital birth defect in boys and affects about 2–4% full-term male neonates. Its etiology is multifactorial. Purpose. To evaluate the serum bisphenol A (BPA) levels in boys with cryptorchidism and healthy boys and to assess the risk of environmental exposure to BPA using the authors’ questionnaire. The data were acquired from a study on boys with cryptorchidism (n=98) and a control group (n=57). Prior to surgery, all patients had BPA serum levels evaluated. The size, position, rigidity of the testis, and abnormality of the epididymis of the undescended testis were assessed. Parents also completed a questionnaire on the risks of exposure to BPA in everyday life. Results. The testes in both groups were similar in size. The turgor of the undescended testis in the group of boys with cryptorchidism was decreased. Free serum BPA level in cryptorchid boys and in the control group was not statistically significant (p>0.05). The conjugated serum BPA level in cryptorchid boys and in the control group was statistically significant (p≤0.05). Total serum BPA level in cryptorchid boys and in the control group was statistically significant (p<0.05). Serum total BPA level was related with a positive answer about problems with conception (p<0.02). Conclusion. Our study indicated that high serum BPA was associated with cryptorchidism.